THEORY OF THE ISSUE OF JUDICIAL LAWMAKING AND NORMATIVE RESOLUTIONS OF THE SUPREME COURT OF THE REPUBLIC OF KAZAKHSTAN - Ryszhanova Гүлнұр Саматовна; Ахмет, Бергенгул; Abdrassulov Ермек Баяхметұлы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2025)
This article provides a comprehensive analysis of the legal nature of the normative resolutions of the Supreme Court of the Republic of Kazakhstan, their place within the national legal system, and their role in the law-making process. The author substantiates that the normative resolutions of the Supreme Court are not only a means of unifying judicial practice but also an essential legal mechanism for the development of national law. The article examines the structural features of these resolutions, their significance in the formation of legal norms, and their position within the legal regulation system from both theoretical and practical perspectives. The normative resolutions of the Supreme Court occupy a unique place in Kazakhstan’s legal system. They play a significant role in eliminating legal gaps and influencing the application of law by interpreting and clarifying legislative provisions. The article also considers scholarly opinions suggesting that these resolutions may, to a certain extent, constitute new legal norms. A comparative and analytical approach is used to assess these views and to explore their theoretical foundations and practical relevance.The research applies formal legal, systemic-structural, comparative-legal, and historical-legal methods. The authors conduct a systematic analysis of the texts of the Supreme Court’s resolutions, their adoption procedures and structures, as well as the legal positions formed through these acts. Furthermore, the judicial law-making practices of Germany, Russia, and Turkmenistan are examined for comparison.The article also addresses the involvement of the judiciary in law-making and its relationship with the legislative branch. Within this context, the status of normative resolutions as sources of law, their legal force, and their place in the hierarchy of normative legal acts are investigated. The author argues for the necessity of legislatively clarifying the legal status of normative resolutions as an integral part of the legal system and offers specific proposals in this regard. This article represents a relevant scholarly contribution aimed at deepening the understanding of judicial law-making and raising the issue of revisiting the legal status of normative resolutions.